2023
DOI: 10.17705/1thci.00084
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Expanded Task-technology Fit Theory and the Technology Acceptance Model: A Multi-wave Empirical Analysis

Abstract: Abstract:For human resource (HR) departments, screening job applicants is an integral role in acquiring talent. Many HR departments have begun to turn to social networks to better understand job candidates' character. Using social networks as a screening tool might provide insights not readily available from resumes or initial interviews. However, requiring access to an applicants' social networks and the private activities occurring therein-a practice currently legal in 29 U.S. states (Deschenaux, 2015)-could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 91 publications
5
25
1
Order By: Relevance
“…This result is consistent with the previous theoretical arguments since numerous authors reported that the hiring managers seek more information available from SNSs (Hosain et al, 2020;Hosain and Liu, 2020a;Pramod and Bharathi, 2016;Ebnet, 2012). On the other hand, PACI had positive influence (β 5 0.038) on PBC (consistent with previous literature) although the influence was not significant (p > 0.05) which is also supported by Drake et al (2016) where the authors revealed that the hiring managers, in many cases did not pay much attention to information accuracy. In case of third hypothesis, PRI had also been proved to have positive (β 5 0.015) (consistent with previous literature) but insignificant (p > 0.05) influence on PBC duly supported by a number of authors (Villeda and McCamey, 2019;Slovensky and Ross, 2012;Dennis, 2011) who argued that the employers do not emphasize on information reliability as much as they should.…”
Section: Discussion Of Results Linking Previous Findingssupporting
confidence: 88%
“…This result is consistent with the previous theoretical arguments since numerous authors reported that the hiring managers seek more information available from SNSs (Hosain et al, 2020;Hosain and Liu, 2020a;Pramod and Bharathi, 2016;Ebnet, 2012). On the other hand, PACI had positive influence (β 5 0.038) on PBC (consistent with previous literature) although the influence was not significant (p > 0.05) which is also supported by Drake et al (2016) where the authors revealed that the hiring managers, in many cases did not pay much attention to information accuracy. In case of third hypothesis, PRI had also been proved to have positive (β 5 0.015) (consistent with previous literature) but insignificant (p > 0.05) influence on PBC duly supported by a number of authors (Villeda and McCamey, 2019;Slovensky and Ross, 2012;Dennis, 2011) who argued that the employers do not emphasize on information reliability as much as they should.…”
Section: Discussion Of Results Linking Previous Findingssupporting
confidence: 88%
“…Forparticipantswhoweretoldthatthehiringorganizationwantedthepasswordtotheirsocial mediaprofile,boththetrustingstanceandsocialmediaproductionhadanimpactonthetrustinthe companyaftertherequest(seeFigure7).RequestinglogininformationforSMaccountswasconsidered themostintrusiveofthethreeexperimentalcontrols.Insuchsituations,theamountofcompetence oftheprofessionalshadnosignificantimpactontheirtrustinthehiringorganization.Thisstandsto reason,sincetrustwasgenerallylowerinthisgroupthaninothergroups,withlittlevariance,making theidentificationofrelationshipsbetweenTrustandotherVariablesdifficult.However,highersocial mediaproductionledtohighertrust,perhapsbecauseparticipantsfelttheyhadnothingtohide. Unsurprisingly, trust was very low in situations where the recruiter asked for social media passwords.Thisisconsistentwithpreviousresearchthatshowsthatsuchrequestsinitiatevarious information privacy protective responses (Drake et al, 2016). In such situations, only the initial trustingstancepredictstheleveloftrustintheorganizationaftertherequest.…”
Section: Analysis and Resultssupporting
confidence: 81%
“…Using stakeholder management theory, we investigate young people's concerns with their publicly available social media data being used in the specific context of job hiring. While previous research has analyzed job candidates reactions to potential employers asking for their social media login information (Drake et al 2016;McEwan and Flood 2017), our research analyzes perceptions of privacy for social media data that is already public and, as such, does not require any login information to obtain. The research is contextually situated at the interplay of the necessity of hiring the best people with limited resources, the organizational response of engaging in social media job screening, and the individual response of people expressing concern.…”
Section: Introductionmentioning
confidence: 99%